Monitoring Cortical and Neuromuscular Activity: Six-month Insights into Knee Joint Position Sense Following ACL Reconstruction - Aglaja Busch; Lorena R. R. Gianotti; Frank Mayer; Heiner Baur (International Journal of Sports Physical Therapy, 2024)
# Background